Slimmer’s paralysis: a case report - Haque, Md Rezwanul; Sharmin, Kazi Sumona; Abdullah, Asif Mohammad; Ahad, Ahad-Ul-Islam; Kundu, Narayan Chandra (BIRDEM Medical Journal, 2026)
Isolated common peroneal neuropathy (CPN) is the most common lower extremity mononeuropathy and the third most common mononeuropathy in adults. It is often associated with multiple causes including trauma, hereditary neuropathies and iatrogenic causes. We report a case of acute bilateral foot drop in a young male following a rapid weight loss attributable to tirzepatide therapy. This case highlights the importance of monitoring for neurological side effects in patients receiving novel glucagon like peptide-1 plus gastric inhibitory polypeptide receptor agonist. BIRDEM Med J 2026; 16(1): 40-43